Implementasi Kepedulian Lingkungan melalui Ekowisata Gua Pindul sebagai Sumber Belajar IPS - Nurlaily Fatayati; Elsa Putri Ermisah Syafril (Proceedings Series on Social Sciences & Humanities, 2022)
Education is one of the media to implement the environmental care. The concept of Gunungkidul's ecotourism is a management activity in the tourism sector while ensuring environmental sustainability as the main requirement. This study aims to discuss: (1) the implementation of environmental awareness in social sciences learning; (2) the implementation of environmental awareness through Gua Pindul ecotourism as social sciences learning resource; (3) the supporting and inhibiting factors of Gua Pindul ecotourism as social sciences learning resource. This research uses qualitative method. Data are collected through observation, interviews, and documentation. Data is analyzed by data reduction, data presentation, and drawing conclusions technique. The results of the study show that: (1) the implementation of environmental awareness in social sciences learning can be done by showing facts to students about the existence of environmental damage due to human activities. This occurrence environmental damage can be anticipated through a correct understanding of sustainable natural management as part of human duty to maintain God's creation. 2) The implementation of environmental awareness through Gua Pindul ecotourism as social sciences learning resource is done by providing opportunities for students to know the conditions around Gua Pindul ecotourism more closely; students are then motivated to be able showing the actions of concerning to environmental awareness through Gua Pindul ecotourism. Thus, the social sciences learning process will encourage the formation of a more meaningful understanding. 3) The supporting factors for Gua Pindul ecotourism as a source of social sciences learning include Gua Pindul Ecotourism is one of the most popular tourist destinations today, Gua Pindul ecotourism can be used as social sciences learning resource related to conservation, utilization, alignment with local communities by maintaining local culture while improving the welfare of the people of Gunungkidul. The inhibiting factors are the limited access to outing classes through Gua Pindul ecotourism for students, the lack of students' understanding about the impact of environmental damage, and the lack of local communities' readiness to face social changes as a result of tourism development in the Gua Pindul ecotourism area.